Description of the first marine-isolated member of the under-represented phylum Gemmatimonadota, and the environmental distribution and ecogenomics of Gaopeijiales ord. nov. - Yu-Qi Ye; Meng-Qi Ye; Xin-Yue Zhang; You-Zhi Huang; Zi-Yang Zhou; Yan-Jun Feng; Zong-Jun Du (mSystems)
ABSTRACT The phylum Gemmatimonadota is widespread but rarely cultured and, in fact, there are only six described species isolated from soil, freshwater, and wastewater treatment. However, no isolates of Gemmatimonadota from marine environment have been described; thus, little is known about the physiology and metabolism of members of the marine lineages. In this study, four novel facultatively anaerobic bacterial strains belonging to Gemmatimonadota were isolated from marine sediments collected from Xiaoshi Island in Weihai, China, using an aerobic enrichment method. The integrated results of phylogenetic and phenotypic characteristics supported that these four strains represent one novel species in a novel genus, for which the name Gaopeijia maritima gen. nov., sp. nov. is proposed, as the first representative of novel taxa, Gaopeijiales ord. nov., Gaopeijiaceae fam. nov. in the class Longimicrobiia. Gaopeijiales was detected in 22,884 out of 95,549 amplicon data sets, mainly from soil. However, the highest mean relative abundances were in sponge (0.7%) and marine sediment (0.35%), showing salt-related character. Most of the Gaopeijiales subgroups potentially belong to the rare bacterial biosphere. The aerobic enrichment in this study could significantly increase the relative abundance of Gaopeijiales (from 0.37% to 2.6%). Furthermore, the metabolic capabilities inferred from high-quality representative Gaopeijiales genomes/MAGs suggest that this group primarily performs chemoorganoheterotrophic metabolism with facultatively anaerobic characteristics and possesses various secondary metabolite biosynthesis gene clusters (BGCs), mirroring those observed in the four novel strains.IMPORTANCEDespite rapid advances in molecular and sequencing technologies, obtaining pure cultures remains a crucial research goal in microbiology, as it is essential for a deeper understanding of microbial metabolism. Gemmatimonadota is a widespread but rarely cultured bacterial phylum. Currently, there are only six cultured strains of this interesting group, all isolated from non-marine environments. Little is known about the physiology and metabolism of members of the marine lineages. Here we isolated and characterized four novel marine strains, and proposed a new order Gaopeijiales within Gemmatimonadota. Furthermore, the global distribution, environmental preference, and metabolic potential of Gaopeijiales are analyzed using public data. Our work enriches the resources available for the under-represented phylum Gemmatimonadota and provides insights into the physiological and metabolic characteristics of the marine lineage (Gaopeijiales) through culturology and omics.